Histopathological Spectrum and Pain Severity in Oral Lesions: A Cross-Sectional Study from a Tertiary Care Center in Pakistan - Faiz un Nisa, Eman Fatima (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Oral lesions, ranging from benign hyperplasia to malignant neoplasms, represent a significant public health concern. Pain is often the first clinical symptom but is underutilized in diagnostic assessment. Objectives: To evaluate the histopathological spectrum of oral lesions and assess the prevalence, severity, and predictors of pain among patients with biopsy-confirmed oral lesions. Material and Methods: This cross-sectional study was conducted at the Pathology Department, Isra University, Hyderabad, with the Nuclear Institute of Medical Radiotherapy (NIMRA), Jamshoro, and included 338 patients with biopsy-proven oral lesions. Sample size was calculated using OpenEpi at 95% confidence, 5% margin of error, and 66.8% expected pain prevalence. Patients of all ages and genders were enrolled; those with recurrent lesions, incomplete data, or systemic pain-modifying conditions were excluded. Pain was rated on a 0–10 numeric scale following the Brief Pain Inventory and MD Anderson Symptom Inventory, and histopathology, lesion site, tumor size, and TNM stage were recorded. Data were analyzed in SPSS v21 using chi-square and logistic regression, with p < 0.05 considered significant. Results: The mean age was 52.3 ± 12.7 years, with 63.9% males. Malignant neoplasms constituted 39.3% of cases. Pain was reported by 68.3% of patients; 12.1% experienced severe pain. Pain severity was significantly associated with histopathological type, lesion location, and TNM stage (p<0.001). Tongue lesions (OR 2.45), tumor size >4 cm (OR 1.75), and limited mouth opening (OR 3.12) were independent predictors of pain. TNM Stage I tumors were inversely associated (OR 0.32, p=0.003). Conclusion: Pain is a frequent and diagnostically relevant symptom in oral lesions, particularly in malignancies. Pain assessment should be routinely integrated into clinical evaluation to facilitate early intervention. Keywords: Oral lesions, histopathology, pain severity, TNM staging